Factors influencing self-protection practices in online shopping among students of higher education institutions in Malaysia - Daud, Nurul Atikaf (2022)
Technology has recently revolutionized consumer shopping experiences, and Malaysia's high internet penetration rate has sparked rapid growth in the local online shopping marketplace in recent years. The ease and simplicity of online shopping also creates a new area for consumer complaints and challenges in consumer protection issues. Limited research has been done on online shopping among young consumers, particularly college students, and from a literary perspective, there have been many studies on online shopping behaviour but very few in self-protection practices. Additionally, challenges in higher shopping online shopping have resulted in a newly emerging area for consumer issues to become more complicated in terms of their rights. As a result of this predicament, consumers become increasingly vulnerable to fraudulent and deceptive marketing in online transactions. This study aims to investigate the self-protection practices in online shopping among students of higher education institutions in Malaysia. Four factors explored were self-efficacy, media of consumer education, safety priority and subjective norm. The theory pertaining to this research is the Social Cognitive Theory. In this study, the quantitative method was employed and the data were collected through a self-administered questionnaire among 400 respondents who have shopped online. The respondents were selected using systematic random sampling. Descriptive analysis was performed to understand the characteristics of the respondents and variables of the determinants of self-protection practices. Outcomes such as frequency, percentage, mean, and standard deviation were applied to every variable using SPSS. The inferential analysis was performed by way of Pearson correlation and multiple linear regression. The outcome revealed that self-efficacy, media of consumer education, safety priority, and subjective norm have a positive and significant relationship with self-protection practices. The result from regression analysis indicated the regression model to be statistically significant due to the significance of F statistics generated (F=78.280: P < 0.05). Meanwhile, these four variables contributed 43.7 percent to the model. The multiple linear regression analysis indicated safety priority as the most influential predictor. This study supports the importance of self-protection practices in online shopping among students of higher educational institutions. This study examines self-protection practices, which is a key component of the National Consumer Policy (NCP). In terms of policy implications, the findings suggests that the self-protection aspects in the NCP should also emphasize consumer rights and responsibilities in online purchase. The practical implications centre on the role of media of consumer education, specifically how social and electronic media can be utilized to disseminate consumer education on online shopping practices. Finally, from the methodological standpoint, the study contributes to the application of Social Cognitive Theory, which is rarely used in consumer self-protection practices studies